Measuring Low Carbon Supply Chain - Muhammad Shabir, Shaharudin; Fernando, Yudi (IGI Global USA, 2018)
The threat of climate change is due to increasing carbon emissions of manufacturing production and transportation. Currently, Government is encouraging manufacturing to reduce carbon emission and conducting Low Carbon Supply Chain Management (LCSCM). In order to solve greenhouse gas emission dilemma, LCSCM is essential for manufacturing firm's stakeholders. Supply chain partners are expected to know the proper measurement of emissions to solve this problem. This study aim is to review literature on how to measure LCSCM. In the past, the concept of Green Supply Chain Management (GSCM) is practiced to promote and reduce environmental risks. However, GSCM is a driver or practice to achieve environmental outcome. The extended model of GSCM has currently practices in LCSCM through Carbon Footprint (CF) concept. In other word, LCSCM is an outcome that both researcher interests and practitioner persuades.